Enhancing Employee Performance through Strategic Artificial Intelligence Initiatives - Indrasari, Meithiana; Pamuji, Eko (PT. Riset Press International, 2024)
In the current dynamic AI environment, it is crucial for organizations to enhance the cooperation between humans and technology in order to enhance employee performance. This research examines strategic steps to thrive in the workplace amid the presence of AI. The study analyzes the symbiotic relationship between employees and AI technology to identify effective strategies that organizations can implement to improve employee performance. The synthesis of empirical data and case studies from various industries is achieved through the utilization of an interdisciplinary framework that includes organizational psychology, technology adoption theory, and strategic management. The analysis focuses on the impact of customized initiatives such as ongoing learning programs, customizable upskilling, and AI-conscious leadership in enabling employees to collaborate effectively with AI and leverage its capabilities to increase productivity and drive innovation. The study highlights the importance of strategically integrating AI and implementing proactive initiatives that allow employees to easily adopt the technology. In addition, it underscores the importance of organizational culture in cultivating a growth mindset that enables AI to drive individual and collective achievement. The study offers an overarching framework for organizations as they navigate artificial intelligence (AI) integration while placing a high emphasis on developing and growing their employees. Implementing these strategic initiatives can enhance business success in the era of artificial intelligence by optimizing employee performance and achieving competitive advantage.